Application of Humid Silica Plus Fertilizer with Various Combinations of Planting Media - Thomson A.S. Girsang; Veny Apriyani; Desti S.N Pasaribu; Lisnawaty Simatupang (Indonesian Journal of Chemical Science and Technology (IJCST), 2019)
Volcanic ash contains minerals needed by soil and plants with the highest composition of total elements, namely Ca, Na, K and Mg, other macro elements in the form of P and S, while micro elements consist of Fe, Mn, Zn, Cu. The layer of volcanic dust that has the potential to contain nutrients for soil fertilization for agriculture can actually only be used about 10 years after the spread of volcanic ash. Soil fertilization can be accelerated if mixed with organic materials such as by using chicken manure fertilizer which has nutrients from chicken manure: N = 1.7%, P2O5 = 1.9%, K2O = 1.5%. Humic acid helps regulate clay and soil improvement, binds and transfers micro elements from the soil to plants, increases water absorption, and stimulates the development of microorganisms in the soil. Therefore, this study was conducted to make humic silica fertilizer in the planting medium by utilizing volcanic ash in combination with chicken manure mixed with soil. In this study apart from being a source of humic acid, chicken manure is also beneficial because it contains microorganisms which will be useful in accelerating the fertilizer incubation process. The composition of the fertilizer mixture used in this study is: volcanic ash sinabung: chicken manure: soil = 20: 50: 30; 30: 50:20; 40: 50: 10. The mixture is stirred evenly and then incubated for 30 days. After 30 days, the nutrient content of these fertilizers was tested and the highest content of the nutrients obtained in the combination was 20:50:30 namely: Organic C-1.35%, N-total 0.2%, P-available 20.16 ppm , K-available 0.527 me / 100g, C / N 6.75%, and humic acid contained in 3.925%